2001
DOI: 10.1093/pasj/53.6.1191
|View full text |Cite
|
Sign up to set email alerts
|

HV Virginis and WZ Sge-Type Dwarf Novae

Abstract: A dwarf nova HV Vir was observed photometrically for eight nights during the outburst in 1992 April -May. The star showed two distinct types of periodic variation: (1) 82.20-min (0.05708 d) double-humped variation with decaying amplitudes during the early stage of the outburst, and (2) 83.80-min (0.05820 d) superhumps in later stages. We attributed the former to "early superhumps", which are only seen in the earliest stage of WZ Sge-type outbursts. The superhump period and evolution of the superhumps, together… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
132
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(141 citation statements)
references
References 268 publications
9
132
0
Order By: Relevance
“…Although these modulations were detected independently by different groups Mendelson et al 1992;Leibowitz et al 1994 and our group), the distinction of these modulations from (ordinary) superhumps should await yet another object. Our result of HV Vir in 1992 was published in Kato et al (2001) following modern interpretation.…”
Section: Early Superhumpsmentioning
confidence: 57%
“…Although these modulations were detected independently by different groups Mendelson et al 1992;Leibowitz et al 1994 and our group), the distinction of these modulations from (ordinary) superhumps should await yet another object. Our result of HV Vir in 1992 was published in Kato et al (2001) following modern interpretation.…”
Section: Early Superhumpsmentioning
confidence: 57%
“…The origin of unique light variations, as well as their evolutionary status, are still in debate (e.g., Osaki, Meyer 2003;Nakata et al 2014; see Kato 2015 for a review). Their observational properties are that (1) the amplitude of the superoutburst is large, exceeding ∼ 6 mag (Howell et al 1995), (2) the interval between the successive superoutbursts (supercycle) is unusually long, typically with a time scale of decades (Kato et al 2001), (3) modulations with double-peaked profiles called early superhumps are observed in the early phase of the superoutburst (Kato 2002), and (4) after the end of the plateau stage, single or multiple rebrightenings are observed (Imada et al 2006). Among them, properties (3) and (4) are considered to be unique to WZ Sge-type dwarf novae and to be the defining characteristics (see Kato 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Send offprint requests to: T. Kato, e-mail: tkato@kusastro.kyoto-u.ac.jp A large fraction of such confusions turned out to be SU UMa-type dwarf novae or WZ Sge-type dwarf novae (Kato et al 2001b). SU UMa-type dwarf novae are a subclass of DNe.…”
Section: Introductionmentioning
confidence: 99%
“…The object was even proposed to be a nova in the Galactic halo. From distant nova candidates, Kato et al (2001b) selected V359 Cen as a candidate for a rarely outbursting dwarf nova. A finding chart of the proposed quiescent counterpart was presented in Duerbeck (1987).…”
Section: Introductionmentioning
confidence: 99%